SAFETY RULES AND ENTREPRENEUR COMMITMENT: IMPORTANT COMPONENTS FOR SME SAFETY PERFORMANCE - Che Mohd Syaharuddin Che Cob; Engku Huda Mursyidah Engku Hassan Ashari; Sakinah Mat Zin; Khamisah Abd Manaf; Rosfatihah Che Mat; W. Nurfahizul Ifwah W. Alias; Iskandar Hasan Tan Abdullah (International Journal of Accounting, Finance and Business, 2023)
Small and medium enterprises (SMEs) are key drivers of economic growth and employment, and they are the backbone of the economy in Malaysia. Occupational safety and health (OSH) is frequently poorly managed in SMEs, putting workers at greater risk of workplace accidents and illness. The main characteristics of such companies are their weak economic status, lack of investment in health and safety, limited knowledge, awareness, and competence of owners/managers that do not promote OSH. In addition, the lack of safety rules and procedures, and low entrepreneur commitment towards worker safety also contributed to the increasing number in this statistic. The goal of this study is to determine the relationship between safety rules and entrepreneur commitment, and safety performance. To collect data, survey questions from previous studies are adopted and customized. The data are analyzed using SPSS version 27 on a sample of 272 SME entrepreneurs. The study's findings show that safety rules and entrepreneur commitment have a significant impact on safety performance. This enables entrepreneurs and scholars to comprehend and make appropriate decisions that can improve safety performance of Malaysian SMEs.